Prescribing characteristics and guideline concordance of antihypertensive western and Chinese patent medicine in Internet hospitals in China: a cross-sectional study - Zhou, Tiantian; Liao, Xing; Zuo, Jiaxin; Han, Fang; Meng, Ruogu; Zhuo, Lin; Liu, Guozhen; Hu, Jing (Frontiers in Pharmacology, 2025)
IntroductionInternet hospitals have emerged as a vital approach for patients seeking treatment for hypertension, with a significant increase in antihypertensive medication prescriptions through these innovative models. However, prescribing characteristics and guideline concordance of these prescriptions remain unclear. This study aim to analyze the prescribing characteristics of Western medicine (WM) and Chinese patent medicine (CPM) for hypertension and assess their concordance with hypertension guidelines in Internet hospitals in China, providing insights for optimizing antihypertensive CPM management.MethodsA cross-sectional analysis was conducted using data from the Yinchuan Internet Medical Regulatory Platform (YIMRP) covering 87 enterprise-led Internet hospitals in China from 1 January 2018, to 31 March 2021. Visits diagnosed with hypertension and prescribed at least one oral antihypertensive medication (either WM or CPM) were included. Guideline concordance was evaluated by comparing prescribed individual antihypertensive WM and CPM in Internet hospitals with international and Chinese hypertension guidelines recommendations. Statistical analyses included descriptive statistics, association rule analysis, and guideline concordance assessment.ResultsAmong the 787,209 visits, 93.75% were prescribed WM alone, 4.72% CPM alone, and 1.52% a combination of CPM and WM. Calcium channel blockers (CCBs) (38.50%) was the most prescribed WM class, with nifedipine (19.67%) being the most common individual medication. Most prescriptions of antihypertensive WM were guideline-concordant. Among CPM prescriptions, only 181 (0.37%) included traditional Chinese medicine (TCM) syndrome diagnoses. Of the 38 prescribed antihypertensive CPM, only 7 were guideline-recommended. The most frequently prescribed CPM were Jiuqiang Naoliqing (17.67%), and Zhenju Jiangya tablet (14.74%), neither of which was recommended by the guidelines. The combinations of two CPM were frequently prescribed, but none of these combinations were recommended by guidelines. The most common dual CPM combination was Jiuqiang Naoliqing + Qiangli Dingxuan tablet/capsule (support 8.65%, confidence 0.44%).ConclusionThe prescribing characteristics of antihypertensive WM in Internet hospitals closely align with those in offline hospitals with relatively satisfactory guideline concordance. However, some issues persist in antihypertensive CPM prescriptions, including the lack of TCM syndrome differentiation, frequent prescription of non-recommended CPM, and duplicate therapies. Strengthening CPM management in Internet hospitals is essential for optimizing hypertension care.